Internatural Activists and the “Blackfish Effect”: Contemplating Captive Orcas’ Protest Rhetoric through a Coherence Frame - Burford, Caitlyn; Schutten, Julie “Madrone” Kalil (Frontiers in Communication, 2017)
The documentary film Blackfish (2013) follows Tilikum, a captive SeaWorld prisoner-orca responsible for the death of trainer Dawn Brancheau and two others. The film has had a profound effect on public perceptions of orca captivity creating the “Blackfish Effect.” Our critical analysis of the film engages Plec’s (2013) internatural communication categories of complicity, implication, and coherence. We argue that the film illustrates the flawed hierarchy within the binary/dualistic system. In deconstructing a dualism, we must recognize the physical power and actions of captive orcas that could be seen as a form of protest rhetoric. The case example of orcas in captivity as a whole illustrates that regarding orcas as unique actors with intelligible behaviors offers a way of understanding how to listen to the more-than-human world. Our article has been one attempt to illustrate how captive orcas can be heard as extrahuman citizens who participate, and even instigate, policy making.